Effects of caffeine on reaction time are mediated by attentional rather than motor processes. - Saville, Christopher W. N.; de Morree, H. M.; Dundon, Neil M.; Marcora, S. M.; Klein, C. (Psychopharmacology, 2018)
Background Caffeine has a well-established effect on reaction times (RTs) but the neurocognitive mechanisms underlying this are unclear. Methods In the present study, 15 female participants performed an oddball task after ingesting caffeine or a placebo, and electroencephalographic data were obtained. Single-trial P3b latencies locked to the stimulus and to the response were extracted and mediation models were fitted to the data to test whether caffeine’s effect on RTs was mediated by its effect on either type of P3b latencies. Results Stimulus-locked latencies showed clear evidence of mediation, with approximately a third of the effect of caffeine on RTs running through the processes measured by stimulus-locked latencies. Caffeine did not affect response-locked latencies, so could not mediate the effect. Discussion These findings are consistent with caffeine’s effect on RTs being a result of its effect on perceptual-attentional processes, rather than motor processes. The study is the first to apply mediation analysis to single-trial P3b data and this technique holds promise for mental chronometric studies into the effects of psychopharmacological agents. The R code for performing the single trial analysis and mediation analysis are included as supplementary materials.